Does COVID-19 and oral, lung cancer have a connection? A insight to future investigation; A literature review. (Bangladesh Journal of Medical Science, 2023)
Even though there has been a significant amount of research conducted on the origin of SARSCoV- 2 (SARS-CoV-2) aetiology, very little is known about the disease’s long-term effects till the date(1). As with previous viral infections, SARS-CoV-2 may raise the risk of developing cancer by altering tumour suppressor genes and expression of various pro-oncogenic proteins. We will conduct a comprehensive review of the available research on it, because an infection with SARS-CoV-2 might have a potential to cause cancer in the long run, researchers are looking at the likelihood of this happening, precisely on likeliness of occurring oral and pulmonary malignancies in this work. We speculate that one of these long-term impacts may be the SARS-carcinogenic CoV-2 virus. The viral proteins Nsp-15 or Nsp-3 are hypothesised to have pro-oncogenic effects when they interact with two essential tumour suppressors, pRB and p53 inhibitors.Bangladesh Journal of Medical Science Vol. 22 No. 01 January’23 Page : 15-21